Reducing Waste in the Delivery System through Lean Distribution: Implications for Social Commerce Logistics - Agustin, Melinda Dwi; Ernawati, Dira (Journal of Social Commerce, 2025)
This paper explores structural inefficiencies that have been engrained into the delivery procedures, a distributor of industrial gas products, in the context of wastage reduction and improvement on logistic responsiveness, by means of adopting lean distribution. An initial inspection identified extended lead time and operational delays based on delays based on waiting and transport inefficiencies as well as redundant motion, which signified a tangled and non-integrated workflow that was document dependant. Combining Process Activity Mapping (PAM), root cause analysis and 5W+1H technique, the work produced vital, non-value-added activities and recommended focused interventions to reinstate process flow and timing purity. The endeavours of the implementation of the lean-based redesign served to cut down the total time of lead by 14.6 per cent largely through removing the actual bottlenecks in the procedure and also making coordinated handovers on a digital platform. In addition to enhancing efficient stages, the research illustrates that lean distribution serves as a form of structural redesign, which shifts the delivery process out of the series of sequential activities to an integrated, real-time, and demand-oriented system. Such findings validate the view that to enhance the logistics performance in this kind of time-sensitive environment, a reduction of waste is not a sufficient condition but rather a planned transition to digitally-assisted, flow-based process configurations.